Compressive active fault systems along the Central Andean piedmont - Macharé Ordoñez, José (2008)
It’s now established that Andean forearc is not concentrating as much tectonic shortening as the foreland since Middle Miocene. GPS measurements are neither available to inform on the long-term deformation across the Andes in Peru and anyway rather describe the elastic response of the Andean forearc to the Nasca-South American Plate convergence. Few neotectonic studies focuses on the Western side of the Andes and little is known about the active deformation in the Central Andes Pacific lowlands (Sébrier et al., 1988). Recent publications mainly improved the description of geomorphic surfaces (Thouret et al. 2007) and cosmogenic dating of the latter show much younger ones than expected (Hall et al., 2008). The topographic gradient on the western side of the Peruvian Andes is quite high as the trench (-7000m) lies only 200km away from the highest point (6000m). Moreover, authors still question the fact that the Andes build through a giant focused monocline or normal fault and demonstrate doing so the need of further mapping of the fault systems on the western side of the Central Andes (Schildgen et al., 2007).